Strategies Used in Online Distance Learning by Grade 12 Humanities Students in Bestlink College of the Philippines : Vol.3, No.1D (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Given the pandemic broad negative effects on students, there is a clear need for information on the best coping methods to aid students in receiving greater support and understanding during the pandemic. This study aims to determine how grade 12 HUMSS students at Bestlink College of the Philippines cope with online distance learning. The researcher wants to know if they have any problems or impediments to learning at home and if they have overcome these obstacles when learning online. This survey also wants to hear what advice they would provide to other students who were having trouble adapting to our new way of learning. The qualitative is the method used by the researchers in conducting this study. Researchers also used Convenience Sampling to gather data from 60 respondents of Grade 12 HUMSS Students. This study found that most students experienced problems during their Online Learning regarding their connection, environment, and technology used. However, this study also revealed that students have a strategy during their Online Learning to cope with the fast-paced learning. In addition, there are some recommendations that they can apply to their selves.